Penerapan Strategi Pembelajaran Afektif dalam Meningkatkan Motivasi Belajar Siswa di Maitreechit Wittayathan School Bangkok, Thailand - Cahya Golbin Aisaroh (Jurnal Dirosah Islamiyah, 2024)
Affective aspects are one of the three aspects that are very Important in learning.Affective aspects are aspects or element of attitudes that have been formed and embedded in a learner.this attitude cannot be separated from value.Every attitude and action,will definitely be valuable. there must be a structured and suitable strategy for affective purposes..This educational institution applies affective learning  strategies to support the interest and motivation of learning of its students.Where by applying affective learning  strategies it goes straight in accordance with the vision and mission of the school,namely “Creating students who have intelligence based on religion and morality.This research method uses a qualitative case study method using interview,observation and documentation data collection techniques using a qualitative approach.Based on the result of the existence of affective strategies makes the nature and attitude of participants.